Кераміка середньовічного Білгорода: матеріали розкопок 1969, 1971 рр. - Тесленко, I.Б.; Мироненко, Л.В. (Археологія, 2022)
У статті репрезентовано окремі зразки побутової
й архітектурної кераміки з розкопок середньовічного Білгорода 1969 і 1971 рр., що зберігаються в
Наукових фондах Інституту археології НАН України. До їх аналізу залучено широке коло порівняльного матеріалу, що разом із результатами останніх
досліджень середньовічних пам'яток Північного
Причорномор'я дало можливість запропонувати
новий погляд на хронологію як самих керамічних
знахідок, так і археологічного контексту, з якого
вони походять. In the focus of the study is pottery together with its archaeological context from the excavations of Bilhorod (Bilhorod-Dnistrovskyi,
Odesa Oblast, Ukraine), led by S. D. Kryzhytskyi in 1969 and 1971. These are 17 items, 15 of which are stored in the
Scientific Repository of the Institute of Archaeology of the NAS of Ukraine. They were found in a section of the medieval site
north-east of the fortress walls in the area of one of the pottery workshops, set up on the ruins of a round antique tower. The previous
researchers of medieval Bilhorod (S. Kryzhytskyi, A. Kravchenko, H. Bohuslavskyi and others) associated a thick medieval
horizon outside the fortress, as well as on the area investigated in 1969 and 1971, with the “Golden Horde” stage in the history of
the city, dating back to the turn of the 13th–14th – the 1370s. They identified three construction periods in its structure, correlated
the earliest one with the functioning of the pottery kilns, and dated back not later than the beginning of the 14th century. However,
a careful study of the excavated material allowed us determining stove tiles of Central European morphological types by the second
half of the 15th century, among the main products of this pottery workshop. Therefore, firstly, the activities of the workshop
cannot be dated earlier than the middle or second half of the 15th century. Secondly, this type of pottery was not inherent in the
“Golden Horde” cultural tradition at all, and therefore cannot be associated with it. The dwellings and other objects on the ruins
of the kilns were built even later. Thus, the remains of ceramic production, as well as subsequent construction, can be correlated
only with the late stages of the “Moldavian” period of Bilhorod’s history, which lasted in general from the end of the 1370s to
1485, but not with the Golden Horde. Related ceramic finds, studied in the Scientific Funds of the Institute of Archaeology of the
NAS of Ukraine, also refer mainly to the 15th century or to the last quarter of the 15th–16th centuries. The latter most likely marks
the time of the destruction of buildings. At the same time, several finds from excavations in 1969 and 1971 (Dzhuchid coins,
fragments of amphorae, and glazed pottery) indicate some anthropogenic activity at the site in the 14th century as well. However,
they mostly do not have a clear context. Therefore, it is quite difficult to localize the stratified archaeological objects of this time
through the data from the reports.